The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.37939/jrmc.v25i3.1616
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Male and Female Medical Student's Motivation towards Career Choice

Abstract: Objective: To compare motivation to become a doctor in both genders Study Design: Observational cross-sectional study Place and Duration of Study:  Rawalpindi Medical University in March 2019. Materials and Methods: First and second-year M.B.B.S students were included in the study. Age, year of study, and gender were recorded.  The questionnaire included 18 questions assessing six motivational dimensions: status and security; nature of the occupation; career opportunities; patient care and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Despite being higher, the ratio was consistent with findings of a nearly 2:1 M: F ratio by Salaam et al 1 However, another study found a M:F ratio of 1:1, while Sattar et al reported a reversed M:F ratio of about 1:2 in favour of females, indicating that the situation for women is improving. 13,14 The reasons behind gender disparities among professionals are diverse and complicated, affecting not just medical institutions but also every facet of society. 15 The incidental gender gap in our research may be due to a shortage of female mentors with expertise in the various medical disciplines to inspire others to pursue the same career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being higher, the ratio was consistent with findings of a nearly 2:1 M: F ratio by Salaam et al 1 However, another study found a M:F ratio of 1:1, while Sattar et al reported a reversed M:F ratio of about 1:2 in favour of females, indicating that the situation for women is improving. 13,14 The reasons behind gender disparities among professionals are diverse and complicated, affecting not just medical institutions but also every facet of society. 15 The incidental gender gap in our research may be due to a shortage of female mentors with expertise in the various medical disciplines to inspire others to pursue the same career.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, separate reports by other researchers suggests that things might be improving for women. 13,14 The primary motivations for wanting to earn a living as radiologists was obvious. More than ever, radiology has become an important link in the medical health chain since it is a service department that provides answers, so physicians often request diagnostic tests even before seeing the patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps because female students tend to have better pre-intervention baseline academic performance than males. [10][11][12][13][14] Thus, it is the male students who seem to have a greater scope of improvement post SBME, due to a lower pre-intervention baseline. However, this observation needs to be further validated through future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…8,11 Recently, it has been reported that the female medical students are more motivated because they have more social reasons for selecting a career in medicine than their male colleagues, and further studies are also recommended at the local level. 12 However, this study has been conducted to determine the gender perspective on motivation to study medicine and the option of future practice.…”
Section: Introductionmentioning
confidence: 99%